CRISPR/Cas9-mediated lipoxygenase gene-editing in yellow pea leads to major changes in fatty acid and flavor profiles - Bhowmik, Pankaj; Yan, Wei; Hodgins, Connor; Polley, Brittany; Warkentin, Tom; Nickerson, Michael; Ro, Dae-Kyun; Marsolais, Frédéric; Domoney, Claire; Shariati-Ievari, Shiva; Aliani, Michel (Frontiers in Plant Science, 2023)
Although pulses are nutritious foods containing high amounts of protein, fiber and phytochemicals, their consumption and use in the food industry have been limited due to the formation of unappealing flavors described as beany, green, and grassy. Lipoxygenase (LOX) enzymes are prevalent among pulse seeds, and their activity can lead to the formation of volatile organic compounds (VOCs) from certain polyunsaturated fatty acids (PUFAs). As a widespread issue, in legumes, including soybean these VOCs have been linked to certain unappealing taste perception of foods containing processed pulse seeds. To address this problem in pea and as proof of principle to promote the wider use of pulses, a Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) construct was designed to create null alleles (knockouts) of PsLOX2 which had been implicated in the generation of VOCs in peas. Successful CRISPR/Cas9-mediated LOX gene editing of stable transgenic pea lines (TGP) was confirmed by DNA sequencing of the wild type (WT) and TGP pslox2 mutant lines. These lines were also assessed for LOX activity, PUFA levels, and VOCs. Compared to WT peas, the TGP lines showed a significant reduction (p < 0.05) in LOX activity and in the concentration of key VOCs, including hexanal, 2-hexenal, heptanal, (E)-2-heptenal, (E, E)-2,4-heptadienal, 1-octen-3-ol, octanal, (E)-2-octenal (E, E)-2,4-nonadienal and furan-2-pentyl. The content of two essential PUFAs, linoleic and α-linolenic acids, the known substrates of LOX in plants, was higher in TGP flours, indicating the efficacy of the CRISPR-mediated gene editing in minimizing their oxidation and the further modification of PUFAs and their products. The collection of VOCs from the headspace of ground pea seeds, using a portable eNose also distinguished the TGP and WT lines. Multiple regression analysis showed that LOX activity correlated with the two VOCs, heptanal and (E, E)-2,4-heptadienal in pea flours. Partial Least Squares Regression plot for selected PUFAs, VOCs, and sensor responses in WT and TGP lines showed distinguished clusters for WT and TGP lines. Together this data demonstrates the utility of CRISPR mediated mutagenesis of PsLOX2 to quickly improve aroma and fatty acid (FA) profiles of pea seeds of an elite Canadian variety.